Optimizing firewall timing for brute force mitigation with random forests - Turmudi Zy, Ahmad; Isarianto, Isarianto; Muhammad Rifa'i, Anggi; Ghofir, Abdul; Dwi Miharja, Muhammad Najamuddin; Tri Sasongko, Ananto (Institute of Advanced Engineering and Science, 2025)
Mitigating brute force attacks remains a critical challenge in cybersecurity, requiring intelligent and adaptive solutions. This research introduces an approach to optimizing firewall deployment timing for enhanced brute force mitigation using pattern recognition techniques with the random forest algorithm. Leveraging the UNSW-NB15 dataset, comprehensive preprocessing and exploratory data analysis (EDA) were performed to ensure the dataset's suitability for machine learning applications. The study utilized a structured workflow, splitting the dataset into training and testing subsets to rigorously evaluate the model's performance. The proposed random forest model achieved a high accuracy of 98.87%, supported by precision, recall, and F1-scores that confirm its effectiveness in distinguishing normal and attack traffic. The confusion matrix further validated the model’s robustness, highlighting its potential in improving the efficiency of firewall deployment. These findings demonstrate the critical role of advanced machine learning techniques in enhancing cybersecurity defenses, particularly in mitigating brute force attacks through optimized, data-driven strategies.